JMJD5 is a human arginyl C-3 hydroxylase - Sarah E. Wilkins; Md. Saiful Islam; Joan M. Gannon; Suzana Markolovic; Richard J. Hopkinson; Wei Ge; Christopher J. Schofield; Rasheduzzaman Chowdhury (Nature Communications, 2018)
Jumonji-C domain containing protein 5 (JMJD5) is essential for animal development but its catalytic activity has remained elusive so far. Here the authors show that human JMJD5 is an arginyl-hydroxylase and present the cofactor, substrate and product bound JMJD5 crystal structures.